Dual fluorescence of 2-(2′-hydroxyphenyl) benzoxazole derivatives via the branched decays from the upper excited-state. Issue 48 (1st December 2021) - Tang, Zhe; Han, Haiyun; Ding, Junxia; Zhou, Panwang
Abstract : A new mechanism involving branched decays from the upper excited-state has been proposed to explain the experimentally observed dual fluorescence of one 2-(2′-hydroxyphenyl) benzoxazole derivative. Abstract : As a special fluorescence phenomenon, double fluorescence has been widely developed and applied in various fields. Nevertheless, most of the research on fluorescence emission channels focuses on the first excited state, while the research on how to control the fluorescence emission channel through the upper excited state is relatively under-explored. Here, we use the time-dependent density functional theory method and consider the 2-(2′-hydroxyphenyl) benzoxazole (HBO) derivative system as an example to study the effect of upper excited states on double fluorescence. According to the calculation results, a new mechanism for the dual fluorescence was proposed, which involved the different decay pathways from the upper excited-state, the internal conversion through vibrational relaxation, and conical intersection, respectively. This research has potential value and can help in determining how to control the fluorescence emission channel through the upper excited state.